Pembekalan Health Education Tentang Antenatal Care (ANC )Terpadu Dalam Masa Pandemic Covid-19 Kabupaten Mojokerto - Ariu, Ariu Dewi Yanti; Asirotul, Asirotul Ma’rifah; Naning, Naning Puji Suryantini; Siti, Siti Indatul Laili; Firda , Firda Muflikhatul (Universitas Merdeka Surabaya, 2023)
Community service is an important means of improving the quality of education and public knowledge about health tips during pregnancy and the importance of carrying out integrated ANC examinations for pregnant women even during the Covid-19 pandemic. Provision of health education is needed during the Covid-19 pandemic, especially for pregnant women. The purpose of this community service is to add insight and knowledge to pregnant women about the importance of Integrated ANC during the Covid-19 pandemic. The activity of providing health education is to create a learning process that leads to education and evaluation activities based on evidence based. The implementation of this community service activity was carried out at PMB (Independent Midwife Practice) in the Mojokerto area randomly selected in three PMBs. The total number of respondents was 50 pregnant women, before being given counseling we gave questionnaires to the audience with the result that most of the pregnant women did not know the importance of Integrated ANC and were afraid to check their pregnancies with health workers during the Covid-19 pandemic. So that some of them did not carry out integrated ANC examinations during the pandemic and chose to stay at home because they were afraid of transmitting the Covid-19 virus. After being given Health Education about the importance of integrated ANC and healthy tips for pregnant women during a pandemic, they finally realized the importance of maintaining the health of mothers and babies, especially having to continue to carry out integrated ANC examinations so they can get quality pregnancy services and detect early any abnormalities/complications in mothers, even though they are in a pandemic while still adhering to health protocols to avoid transmission of Covid-19.